Peran Perkumpulan Ruang Belajar Aqil Terhadap Pemberdayaan Masyarakat Dalam Usaha Penguatan Literasi ( Studi Pada Mi Hasyim Asy’ari, Desa Talangsuko, Kecamatan Turen, Kabupaten Malang) - Sudariyanto, Anin Dyas; Kriswibowo, Arimurti (Peneliti.net, 2024)
The role of non-governmental organizations (NGOs) in community empowerment has increasing urgency, especially with current issues that must be resolved immediately. The role of non-governmental organizations (NGOs) is viewed from the purpose of why the organization was formed. NGOs can provide education, provide skills training and support inclusive education programs through community empowerment. The purpose of this study is to determine the extent to which the Aqil Learning Space Association can empower the community to be more actively involved in improving knowledge and skills at the research locus. The data sources used in this research are primary data and secondary data. Primary data is obtained directly from the object under study by conducting interviews with MI Hasyim Asy'ari students and teachers at MI Hasyim Asy'ari. The results of this study indicate that the Aqil Study Room Association plays a role in strengthening literacy in MI Hasyim Asy'ari with the reading degree program which is the most widely implemented and succeeds in fostering students' interest in reading seen from the impressions and messages given. However, there are several obstacles that cause the process of strengthening literacy to be less than optimal due to the limited time given only during the internship period. So that the absence of a sustainable program will hinder the process of community empowerment itself.